The causal relationship between the human gut microbiota and pyogenic arthritis: a Mendelian randomization study - Bai, Boliang; Luo, Longfei; Yao, Feng; Sun, Qian; Chen, Xingguang; Zheng, Wen; Jiang, Lang; Wang, Xiaodong; Su, Guanghao (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundRecent studies have indicated the role of the gut microbiota in the progression of osteoarticular diseases, however, the causal relationship between the gut microbiota and pyogenic arthritis remains unclear. There is also a lack of theoretical basis for the application of the gut microbiota in the treatment of pyogenic arthritis.MethodsIn our study, we utilized the largest genome-wide association study (GWAS) data from the MiBioGen Consortium involving 13,400 participants and extracted summary statistical data of the microbiota metabolic pathways of 7,738 participants of European descent from the Dutch Microbiome Project (DMP) The data of pyogenic arthritis were derived from the FinnGen R10 database, including 1,086 patients and 147,221 controls. We employed the two-sample Mendelian randomization approach to investigate the causal association between the gut microbiota and pyogenic arthritis. Our methods comprised inverse variance weighting, Mendelian Randomization Egger regression, weighted median, and weighted modal methods. Subsequently, polygenic and heterogeneity analyses were conducted.ResultsAt the class level, β-proteobacteria is positively correlated with the risk of pyogenic arthritis. At the order level, Burkholderia is positively associated with the disease. At the genus level, the unclassified genus of Sutterellaceae is positively correlated with the disease, while the unnamed genus of Lachnospiraceae, Rothia, and the unnamed genus of Erysipelotrichaceae are negatively correlated with the disease. In addition, Faecalibacterium and Finegoldia are also negatively correlated with the disease. Sensitivity analysis did not show any abnormal evidence.ConclusionThis study indicates that β-proteobacteria, Burkholderiales, and the unclassified genus of Sutterellaceae are associated with an increased risk of the disease, while the unnamed genus of Lachnospiraceae, Rothia, the unnamed genus of Erysipelotrichaceae, Faecalibacterium, and Finegoldia are related to a reduced risk. Future studies are needed to elucidate the specific mechanisms by which these specific bacterial groups affect pyogenic arthritis.